Replacement Refrigerants for Water Chillers - Ian Maclaine-cross (Mesin, 1999)
The Montreal Protocol requires large water chillers cease using refrigerants 11, 22 and 123. Comparing thermodynamic and transport property parameters for these, 134a, 290, 601, 601a, 717 and pentaï¬uoroiodoethane avoids certain errors and biases. The parameters for R71 7 (ammonia) offer energy savings about 20%. R290 or 717 can replace 22. The pentane mixture R601 /601a [50/50] with an electronic 38% rotor speed increase can economically replace R11.